Patient Perspectives of Rural Kansas Maternity Care - Blythe, Meghan; Kathryn Istas; Shane Johnston; Jasmine Estrada; Maci Hicks; Michael Kennedy, M.D. (Kansas Journal of Medicine, 2021)
Introduction. Pregnant women in rural areas face a unique set of challenges due to geographic maldistribution of obstetric services. The perspectives of rural Kansas women were sought regarding experience of birth and satisfaction with maternity care.Methods. Medical student research assistants facilitated discussion groups in rural Kansas communities with women who had given birth in the last 24 months. Guiding questions were used to facilitate discussion. Survey instruments were used to gather information about satisfaction with maternity care. Data for qualitative and quantitative analysis was aggregated using Rural Urban Commuting Area (RUCA) codes.Results. 14 groups with 47 total participants completed the survey and discussion. Participants were representative of a variety of Large Rural, Small Rural, and Isolated areas in Kansas as described by RUCA Code Four Category Classification. Survey results indicate that satisfaction with maternity care in participants’ home county was significantly higher in Small Rural and Isolated compared to Large Rural RUCA. Qualitative analysis results show positive experiences related to: doctor characteristics, relationship with doctor, doctor’s involvement with care, alternative labor options, and distance convenience. Negative experiences were related to: doctor bedside manner, doctor not there until delivery, and staff related complaints.Conclusions. Women in Small Rural and Isolated RUCA codes appear to be more satisfied with care contrary to previous study findings.